Governance Model for Artificial Intelligence in the Public Sector of Guayaquil, Ecuador, 2024 - Prieto, Elisa Amelia Cisneros; Galarza, Ingrid Angelina Soto; Guevara, Antonio Poveda; Sanchez , Shamary Poleth Valdospin; Calderón, Ricarte Francisco Carreño (Journal of Ecohumanism, 2024)
Background: The implementation of artificial intelligence (AI) in the public sector represents a crucial milestone in the digital transformation of Ecuador, particularly in Guayaquil. While AI has the potential to optimize administrative processes, enhance public services, and improve data-driven decision-making, its deployment without a robust governance framework poses ethical, legal, and social risks. Methods: This study employs a quantitative, non-experimental research design to analyze AI governance in Guayaquil’s public administration. Data collection was conducted through structured surveys administered to public employees, evaluating key dimensions such as governance components, public perceptions, technological infrastructure, and ethical considerations. Statistical techniques, including Pearson correlation analysis, were used to assess relationships between variables. Results: Findings highlight the disparity in AI adoption among public institutions, with significant gaps in training, infrastructure, and policy implementation. The study underscores the necessity of an AI governance model that ensures transparency, inclusivity, and ethical compliance. Conclusions: The proposed governance model provides strategic recommendations for AI adoption in Guayaquil’s public sector, emphasizing regulatory frameworks, capacity-building initiatives, and cross-sector collaboration. This research contributes to the global discourse on responsible AI governance, aligning with international efforts to establish ethical standards for emerging technologies